The static time of the manufactured template deviates the accuracy of implant surgery: A retrospective cohort study - LUO Yilin; LAN Dongping; MAN Yi (Kouqiang hemian waike zazhi)
[Objective:] To investigate the potential impact of surgical templates manufactured 7 days before the surgery on the accuracy of implants. The findings will serve as a valuable reference for clinical practice. [Methods:] A total of 104 patients and 164 implants were included in this study, and they were divided into two groups based on the time elapsed since template production：group 1 (≤7 days) and group 2 (>7 days). Subsequently, each group was divided into subgroups based on the different implantation sites in patients. The errors of implant placement were measured accordingly. Statistical analysis was performed using the Mann‐Whitney U test. [Results:] Group 1 included 86 implants, while group 2 included 78 implants. There was a statistically significant difference in apical deviation between the two groups (P<0.05). Additionally, significant increases in apical deviation were found in mandibular cases, distal‐extension edentulous cases, continuous edentulous cases, and cases involving anchor pin installation (P<0.05). [Conclusion:] The analysis of the data suggests that when the time elapsed since template production exceeds seven days, there is an increase in the apical deviation of the implant in cases involving mandibular, distal‐extension partial edentulism, and continuous partial edentulism.